Analisis Kemampuan Pemecahan Masalah Siswa pada Materi Statistika dengan Menggunakan Model PBL - Lebunga, Maria Anita; Towe, Mariana Marta (Papanda, 2025)
The type of research used is qualitative research. The data collection methods employed by the researcher were written tests, interviews, and documentation, while the data analysis techniques included data reduction, data presentation, and conclusion drawing. This study aims to: (1) describe the mathematics learning process on the statistics topic using the Problem-Based Learning (PBL) model; and (2) describe students’ problem-solving abilities in the statistics topic after participating in learning using the Problem-Based Learning (PBL) model. The research was conducted at SMPN 3 Tanjung Bunga from January to June 2025. The subjects in this study were eighth-grade students of SMPN 3 Tanjung Bunga in the 2025/2026 academic year. The data analysis techniques used were data reduction, data presentation, and conclusion drawing.The results showed that, based on the written test conducted with 9 students after participating in mathematics learning using the Problem-Based Learning (PBL) model: for Problem 1, out of 9 students, 7 students were able to achieve indicators 1–4, and 2 students only achieved indicator 1 in problem-solving ability. For Problem 2, all 9 students were able to achieve indicators 1–4 of problem-solving ability. For Problem 3, 7 students were able to achieve indicators 1–4 of problem-solving ability, while 2 students only achieved indicators 1–3 of problem-solving ability.